Peran Sistem Ententerprise Resource Planning dalam Meningkatkan Kualitas Laporan Keuangan Perusahaan - Fahmi Ilham; Sephia, Sephia; Syifa Azkia Marwah; O. Feriyanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the role of the Enterprise Resource Planning system in improving the quality of corporate financial reports. Accurate, relevant, and timely financial reports are the main key to effective decision making by management and stakeholders. However, many companies, especially in Indonesia, still face obstacles in preparing financial reports due to manual processes that are prone to errors, information delays, and lack of data integration. The Enterprise Resource Planning system as an integrated information technology solution is expected to be able to overcome these problems by automating business processes and providing data in real time. The research method used is a literature review that examines various sources of scientific literature related to the implementation of Enterprise Resource Planning and its impact on the quality of financial reports. The results of the study indicate that the implementation of Enterprise Resource Planning significantly improves the accuracy, efficiency, relevance, and timeliness of financial report preparation, while supporting data transparency and accountability. Constraints such as limited human resources, implementation costs, and resistance to change remain challenges that must be managed properly. This study concludes that Enterprise Resource Planning has a strategic role in improving the quality of financial reports and is an important investment for companies that want to increase their competitiveness and effectiveness of financial management in the digital era.